Differentiation of high-grade-astrocytomas from solitary-brain-metastases: Comparing diffusion kurtosis imaging and diffusion tensor imaging. Issue 12 (December 2015) - Tan, Yan; Wang, Xiao-Chun; Zhang, Hui; Wang, Jun; Qin, Jiang-Bo; Wu, Xiao-Feng; Zhang, Lei; Wang, Le
Abstract: Objective: To compare the value of MRI diffusion kurtosis imaging (DKI) and diffusion tensor imaging (DTI) in differentiating high-grade-astrocytomas from solitary-brain-metastases. Methods: Thirty-one high-grade-astrocytomas and twenty solitary-brain-metastases were retrospectively identified. DKI parameters [mean kurtosis (MK), radial kurtosis (Kr), and axial kurtosis (Ka)] and DTI parameters [fractional anisotropy (FA) and mean diffusivity (MD)] values with and without correction by contralateral normal-appearing white matter (NAWM) in the tumoral solid part and peritumoral edema, were compared using the t -test. Receiver operating characteristic (ROC) curves were used to test for the best parameters. Results: The DKI values (MK, Kr, and Ka) and DTI values (FA and MD) in tumoral solid parts did not show significant differences between the two groups. Corrected and uncorrected MK, Kr, and Ka values in peritumoral edema were significantly higher in high-grade-astrocytomas than solitary-brain-metastases, and MD values without correction were lower in high-grade astrocytomas than solitary-brain-metastases. The areas under curve (AUC) of corrected Ka (1.000), MK (0.889), and Kr (0.880) values were significantly higher than those of MD (0.793) and FA (0.472) values. The optimal thresholds for corrected MK, Kr, Ka, and MD were 0.369, 0.405, 0.483, and 2.067, respectively. Conclusion: DKI and directional analysis could lead to improved differentiation with better sensitivity and directional specificity than DTI.